Developing a practical trial for sustainable wetland management based on the environmental and socio-economic functions of melaleuca cajuputi in the Mekong delta - Duong, Van Ni (2000)
This study exammines thr scientific basic for integration of the environmental and socioeconomic functions of Melaleuca into farming systems and trials a model to achieve this end,...